Detection and Prevention of Selective Forwarding-Based Denial-of-Service Attacks in WSNs. (25th August 2013) - Cho, Youngho; Qu, Gang
Abstract : Designing wireless sensor networks (WSNs) that can work reliably in the presence of inside packet drop attackers is very challenging. Current trust mechanisms and avoidance approaches are promising but have their limitations. Avoidance approaches transmit multiple copies of the packets to avoid attackers and cause high overhead. In trust mechanisms, each sensor monitors it neighbors, evaluates their trustworthiness, classifies them as either trustworthy or untrustworthy, and then discards untrustworthy sensors from the network. However, malicious insiders, which are legitimate members of the network and know exactly what their monitoring nodes know, can launch attacks carefully to avoid being detected and discarded from the network. In this paper, we first show that this is possible by introducing a selective forwarding-based denial-of-service (DoS) attack. We then propose an enhanced trust mechanism to detect such attackers and identify their victims. Furthermore, we design two attacker-aware protocols to reroute victim nodes' packets by avoiding the attackers. We conduct extensive OPNET simulations to validate our claims and demonstrate the advantages of our proposed approaches. Finally, as a complementary defensive method to our detection and avoidance approaches, we introduce a prevention routing algorithm that proactively prevents the attack and provide our preliminary results to evaluate its performance.